Pengaruh bunga, citra-merek dan kualitas layanan kredit usaha rakyat BRI terhadap keputusan nasabah di Surabaya - Nafila Nur Diana (STIE Perbanas Surabaya, 2018)
This study aims to describes (1) whether the interest rate of KUR of Bank BRI has a significant effect on the decision to borrow micro business customers in Surabaya (2) whether the brand image of KUR of Bank BRI has a signifi cant effect on the decision of borrowing micro business customers in Surabaya (3) whether the service quality of the KUR of Bank BRI has signifi cant infl uence to the decision of borrowing micro business customers Surabaya (4) whether the interest rate, brand image, and service quality have a signifi cant effect on the decision of borrowing micro business customers in Surabaya. The population in this study are customers of Bank BRI Surabaya. The selected sample is the micro business customers in Surabaya using the KUR product from Bank BRI Surabaya, which is calculated using purposive sampling and run into 110 respondents. The data were collected using methods used in this study is through o questionnaires. The sample was taken using a multiple linear regression method. The results show that interest rates, brand image, and quality of services of KUR of Bank BRI, both partially and simultaneously have a signifi cant infl uence on the decision to borrow micro business customers in Surabaya. These results explain that changes in interest rates, brand image and the quality of services offered by Bank BRI through small business loans can have an impact on the decision of micro business customers residing in Surabaya for lending.